Miscellaneous taxonomic and nomenclatural notes on Microlicia D.Don (Melastomataceae) - Romero, Rosana; Alves Versiane, Ana Flávia; Woodgyer, Elizabeth M. (Phytotaxa, 2022)
Continuing the taxonomic and nomenclatural studies of the genus Microlicia, we propose 44 synonyms for 15 Brazilian species. Of these synonyms, 27 are species and 17 are varieties described in the 19th or early 20th century. Microlicia castrata, M. oxyanthera and M. oxyanthera var. albiflora are synonymized under M. acuminata; M. avicularis var. subspathulata and M. myrtifolia under M. avicularis; M. burchelliana and M. albida under M. cryptandra; M. euphorbioides var. ionantha, M. euphorbioides var. leucantha, M. euphorbioides var. humilis, M. euphorbioides var. parvifolia, M. euphorbioides var. setosa and M. oblongifolia under M. euphorbioides; M. seringeana, M. hilariana, M. leucantha and M. leucantha var. purpurea under M. graveolens; M. euphorbioides var. brevifolia, M. euphorbioides var. macrocarpa and M. helvola var. hirsuta under M. helvola; M. fasciculata, M. decussata, M. cinerea, M. cinerea var. oblongifolia and M. cinerea var. ovata under M. hirsuta; M. depauperata, M. francavillana, M. pallida, M. goyazensis, M. paraensis, M. insignioides, M. alvarengae and M. alvarengae var. glabrata under M. insignis; M. carrasci under M. luetzelburgii; M. semiriana under M. lutea; M. fulva, M. cardiophora and M. martialis under M. serpyllifolia; M. setosa var. aristata, M. sellowiana var. ciliata and M. reichardtiana under M. setosa; M. schreinerii under M. taxifolia; M. variolosa var. glabra and M. peruviana under M. variolosa, and M. gardneri and M. vestita var. densifolia under M. vestita. We also designate 37 lectotypes and propose two new combinations: Microlicia hirsuta for M. variolosa var. hirsuta and the new name Microlicia raymondii for Lavoisiera harleyi.